2011
DOI: 10.1007/s11434-011-4863-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis of 9 heat shock protein genes throughout the life cycle and under abiotic stress in rice

Abstract: Plant heat shock proteins (Hsps) facilitate protein folding or assembly under diverse developmental and adverse environmental conditions. Nine OsHsps were identified in our previous study from a proteomic analysis of rice cv. IRAT 109 leaf samples at the seedling stage under drought stress. To obtain additional information on the 9 OsHsp genes, this study focused on an expression profile analysis at different development stages throughout the life cycle of rice, and under different abiotic stresses and phytoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…It has been reported that endogenous ABA regulated HSP70 synthesis in the leaves and roots of maize seedlings exposed to drought, heat, and combined drought and heat stress, which implied that ABA may improve plant tolerance to stress by increasing HSP70 expression (Heikkila et al 1984;Cho et al 2006;Hu et al 2009;Ye et al 2012). Recently, ABA-inducible sHSP genes were also identified in rice and Capsella bursa-pastoris.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that endogenous ABA regulated HSP70 synthesis in the leaves and roots of maize seedlings exposed to drought, heat, and combined drought and heat stress, which implied that ABA may improve plant tolerance to stress by increasing HSP70 expression (Heikkila et al 1984;Cho et al 2006;Hu et al 2009;Ye et al 2012). Recently, ABA-inducible sHSP genes were also identified in rice and Capsella bursa-pastoris.…”
Section: Discussionmentioning
confidence: 99%
“…In plants Hsp90 have been identified from Pharbitis nil [10], Brassica napus [11], [12], Secale cereale [13], Zea mays [14], Hordeum vulgare [15], Arabidopsis thaliana [16], [17], [18], Oryza sativa [19], [20], [21], Glycine max [22] and Vitis vinifera [23], and most are strongly induced by various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…HSP70 generally functions as a molecular chaperone; i.e., preventing the accumulation of and assisting in the re-folding of proteins under the conditions of stress. The role of HSP70 in relation to heat tolerance has been reported in several crop plants such as soybean [Glycine max (Ortiz and Cardemil, 2001)], wheat [Triticum aestivum (Duan et al, 2011)], tomato [Solanum lycopersicum (Fender and O'Connell, 1989)], and creeping bentgrass [Agrostis palustris (Ye et al, 2012)]. HSP70 also plays a regulatory role in the stress-associated expression of other genes (Lee and Sch€ offl, 1996).…”
mentioning
confidence: 99%